2020
DOI: 10.3390/medicina56020058
|View full text |Cite
|
Sign up to set email alerts
|

5-Lipooxygenase Derivatives as Serum Biomarkers of a Successful Dietary Intervention in Patients with NonAlcoholic Fatty Liver Disease

Abstract: Background: It was previously shown that a bodyweight reduction among patients with nonalcoholic fatty liver (NAFLD) was connected to the lower concentration of arachidonic and linoleic acid derivatives in their blood. We hypothesized that the concentration of these lipids was correlated with the extent of their body mass reduction and, thus, liver steatosis. Methods: We analyzed 68 individuals who completed the dietary intervention. Patients were divided into two groups depending on their body mass reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Moreover, 6 month dietary intervention improved hepatic steatosis paralleled by a decrease in the levels of the eicosanoids analyzed [60]. Similar findings were reported in a larger cohort, wherein dietary intervention that reduced body mass by ≥7% was accompanied by a significant improvement in steatosis paralleled by reduced plasma levels of the measured 5-LOX metabolites (LXA4 and 5-oxo-eicosatetraenoic acid, 5-oxo-ETE) [63].…”
Section: Trends In Pharmacological Sciencessupporting
confidence: 80%
See 1 more Smart Citation
“…Moreover, 6 month dietary intervention improved hepatic steatosis paralleled by a decrease in the levels of the eicosanoids analyzed [60]. Similar findings were reported in a larger cohort, wherein dietary intervention that reduced body mass by ≥7% was accompanied by a significant improvement in steatosis paralleled by reduced plasma levels of the measured 5-LOX metabolites (LXA4 and 5-oxo-eicosatetraenoic acid, 5-oxo-ETE) [63].…”
Section: Trends In Pharmacological Sciencessupporting
confidence: 80%
“…LOX signatures in NAFLD/NASH and ALD/ASH Studies have identified metabolomic signatures, including LOX-derived eicosanoids, that are associated with different disease stages of NAFLD [58][59][60][61][62][63][64]. Puri and colleagues performed comprehensive analysis of eicosanoids in NAFLD, NASH patients, and lean controls, and found that increased levels of 5-, 8-, and 15-HETE were associated with progression from normal to NAFL to NASH, whereas 11-HETE levels were significantly increased in NASH patients alone [58].…”
Section: Trends In Pharmacological Sciencesmentioning
confidence: 99%
“…A reduction of body mass by more than 7% but not less than 7% of total body weight resulted in a significant improvement in steatosis stage, waist circumference, fatty liver index, and levels of triglycerides, cholesterol, as well as 5-lipoxygenase products: 5-oxo-ETE and LX A 4 . Liver steatosis and insulin resistance were significantly associated only with two eicosanoids-5-HETE and 5-oxo-ETE (also products of 5-lipooxygenase) [20].…”
Section: Discussionmentioning
confidence: 97%
“…The selected 37 potential oxylipins were further subjected to classical univariate ROC curve analyses, and the results showed that there were 36 oxylipins with ROAUC > 0.8 (detailed information is listed in Table S13), containing the reported potential biomarkers LXA4 and oxo-ETE. 7 In addition, four new oxylipins containing the upregulated 2-HOTrE (AUROC = 0.86) and the down-regulated 13-HpODE (AUROC = 0.90), 15-HpETE (AUROC = 0.88), and 13-HpOTrE (AUC = 0.83) were discovered as potential biomarkers for NAFLD study. It is recognized that different biomarkers are needed for monitoring NAFLD progression or regression, predicting or assessing treatment response, prognostication, monitoring treatment safety, and evaluating disease susceptibility.…”
Section: Lc-ms/ms Analysismentioning
confidence: 99%
“…6 Among the redox homeostasis and oxidative damage, oxylipin formation and level changes are implicated in the disease state of NAFLD. 7 The proinflammatory lipid mediators (i.e., PGE2 and PGF2a) are altered in NAFLD and proved to contribute to its pathogenesis. 8 Therefore, the lipid mediators, oxylipins, are potential new biomarkers for diagnosis of NAFLD.…”
mentioning
confidence: 99%